Uso consapevole di software speditivi per la ricostruzione 3D - Nocerino, Erica; Remondino, Fabio (GEOmedia, 2016)
The availability of fully automated photogrammetric software allows almost anyone with a camera, even low-quality mobile phones, to generate 3D models for various purposes. Researchers and practitioners employ photogrammetry as a means of 3D reconstruction for excavation and archaeological units, museum artefacts, monuments, cities, landscapes, etc. However, the majority of image-based users are often unaware of the strengths and weakness of the used software, employing it much like a black-box where they can drop photographs in one end, and retrieve a completed 3D models on the other end. Structure from Motion (SfM) methods and software have nevertheless changed the way many people concive the 3D reconstruction approach and are nowadays providing the possibility to digitally model any scene.